Pemodelan Survival Pasien Covid-19 dengan Hazard Non-Proporsional - Rahmat Hidayat; Marwan Sam; Ridha Yulyani Wardi; M. Ishaq Iskandar (Universitas Negeri Gorontalo, 2022)
This article compares two survival models namely Extended Cox and Stratified Cox. These two survival models are alternative models if the proportional assumption of the Cox proportional hazard model is not met. The comparison of the models was carried out using data on the resilience of Covid-19 patients in Palopo City, South Sulawesi. After modeling using the Extended Cox and Stratified Cox models, the AIC values are compared to see a better model. The results obtained indicate that modeling the resilience of Covid-19 patients in Palopo City is better by using Stratified Cox.